2011
DOI: 10.1177/1470320310392097
|View full text |Cite
|
Sign up to set email alerts
|

Dual therapy versus monotherapy of trandolapril and telmisartan on diabetic nephropathy in experimentally induced type 2 diabetes mellitus rats

Abstract: Objective: To investigate the combination of telmisartan with trandolapril therapy versus monotherapy of trandolapril and telmisartan on diabetic nephropathy in type 2 diabetes mellitus rats. Material and methods: Neonatal rats (2 days old) were used for inducing type 2 diabetes mellitus. Streptozotocin at a dose of 90 mg/kg, in freshly prepared citrate buffer (0.1M, pH 4.5), was injected intraperitoneally. There were five groups: (1) normal control, (2) diabetic control, (3) diabetic treated with telmisartan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Therefore, results from experimental studies indicate that inhibition of Ang II receptor activity is associated with beneficial renal effects, suggesting that modulation of this cytokine may have a real clinical application for the treatment of DN. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, results from experimental studies indicate that inhibition of Ang II receptor activity is associated with beneficial renal effects, suggesting that modulation of this cytokine may have a real clinical application for the treatment of DN. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…Пролиферацию мезангиальных клеток и увеличение синтеза внеклеточного матрикса стимулируют α-SMA и TGF-β1, в результате чего оба фактора были идентифицированы как ключевые медиаторы клубочковой и тубулоинтерстициальной патологии при хронических заболеваниях почек [15]. Возрастание концентрации TGF-β1 наблюдают при нефропатии, обусловленной индуцированным сахарным диабетом у крыс [16]. Однако в нашем исследовании возрастание концентрации TGF-β1 в сыворотке крови крыс происходило у всех 450-дневных крыс независимо от диеты.…”
Section: Discussionunclassified
“…Similarly to the fibronectin excretion in the urine per mg creatinine, it has slightly decreased in the groups treated diabetic rats compared to untreated diabetic rats, while the concentration of FN in plasma of rats in all groups examined were in similar extent. Rao et al [ 23 ] giving the rats streptozotocin diabetes ACEi and AT1 blocker received separately and together decrease the concentration of FN in the plasma.…”
Section: Discussionmentioning
confidence: 99%
“…In other groups of diabetic rats receiving treatment, a decreasing trend of albuminuria has been shown in relation to untreated diabetic rats. Rao et al [ 23 ] demonstrated reduction in daily urinary albumin excretion in treated diabetic rats compared to untreated diabetic rats.…”
Section: Discussionmentioning
confidence: 99%